Study on the construction technology of β-alanine synthesizing Escherichia coli based on cellulosome assembly - Lu, Jie; Wang, Guodong; Yang, Cuiping; Peng, Zehao; Yang, Lu; Du, Bowen; Guo, Chuanzhuang; Sui, Songsen; Wang, Jianbin; Li, Junlin; Wang, Ruiming; Wang, Junqing (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: β-Alanine is the only β-amino acid in nature; it is widely used in food additives, medicines, health products, and surfactants. To avoid pollution caused by traditional production methods, the synthesis of β-alanine has been gradually replaced by microbial fermentation and enzyme catalysis, which is a green, mild, and high-yield biosynthesis method. Methods: In this study, we constructed an Escherichia coli recombinant strain for efficient β-alanine production using glucose as the raw material. The microbial synthesis pathway of L-lysine-producing strain, E. coli CGMCC 1.366, was modified using gene editing by knocking out the aspartate kinase gene, lysC. The catalytic efficiency and product synthesis efficiency were improved by assembling key enzymes with cellulosome. Results: By-product accumulation was reduced by blocking the L-lysine production pathway, thereby increasing the yield of β-alanine. In addition, catalytic efficiency was improved by the two-enzyme method to further increase the β-alanine content. The key cellulosome elements, dockerin (docA) and cohesin (cohA), were combined with L-aspartate-α-decarboxylase (bspanD) from Bacillus subtilis and aspartate aminotransferase (aspC) from E.coli to improve the catalytic efficiency and expression level of the enzyme. β-alanine production reached 7.439 mg/L and 25.87 mg/L in the two engineered strains. The β-alanine content reached 755.465 mg/L in a 5 L fermenter. Discussion:The content of β-alanine synthesized by constructed β-alanine engineering strains were 10.47 times and 36.42 times higher than the engineered strain without assembled cellulosomes, respectively. This research lays the foundation for the enzymatic production of β-alanine using a cellulosome multi-enzyme self-assembly system.